2021
DOI: 10.1021/acs.langmuir.1c00417
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Dynamics of Water at the Phospholipid Bilayer Depending on the Head Groups Studied by Molecular Dynamics Simulations

Abstract: Hydration states are a crucial factor that affect the self-assembly and properties of soft materials and biomolecules. Although previous experiments have revealed that the hydration state strongly depends on the chemical structure of lipid molecules, the mechanisms at the molecular level remain unknown. Classical and density-functional tight-binding (DFTB) molecular dynamics (MD) simulations are employed to determine the mechanisms underlying dissimilar water dynamics between lipid membranes with phosphatidylc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 48 publications
4
30
0
Order By: Relevance
“…Although terahertz spectroscopy has been used to analyze TMAO, urea, and sugars independently, there are no reports comparing various osmolytes under the same conditions, and the relation between water molecular dynamics and protein stability is still a mystery. Using MD simulations and THz spectroscopy, one of the present authors have shown that the rotational dynamics of water in solutions can be faster than that of bulk water, even when there is strong hydrogen bonding between the solute and water. , In other words, the long-range structure of water can be broken even when each hydrogen bond is strengthened. Therefore, terahertz spectroscopy may help resolve the puzzling aspects of water-structure-making/breaking.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…Although terahertz spectroscopy has been used to analyze TMAO, urea, and sugars independently, there are no reports comparing various osmolytes under the same conditions, and the relation between water molecular dynamics and protein stability is still a mystery. Using MD simulations and THz spectroscopy, one of the present authors have shown that the rotational dynamics of water in solutions can be faster than that of bulk water, even when there is strong hydrogen bonding between the solute and water. , In other words, the long-range structure of water can be broken even when each hydrogen bond is strengthened. Therefore, terahertz spectroscopy may help resolve the puzzling aspects of water-structure-making/breaking.…”
Section: Introductionmentioning
confidence: 75%
“…This means that the slow relaxation mode measured in this study is only from bulk-like water. Since some water molecules become hydration water and will not be observed in the THz region, the signal from bulk-like water and ε″ both decrease according to the amount of hydration water. ,, On the other hand, it has also been reported that ε″ could increase in the THz region, indicating that the slow relaxation is shifted to a higher frequency, which corresponds to the acceleration of rotational dynamics. , The acceleration will be discussed later. If we look at the fast relaxation mode due to collision dynamics, it can also be affected by solutes, and the strengthening of this mode indicates solute-induced isolation of water molecules from the hydrogen bond network.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure schematically illustrates the lipid bilayer structure using hydrated dimyristoylphosphatidylcholine (DMPC) lipids as a model. In the hydrophilic surface of the bilayer, the interfacial water layers have an approximate thickness of ∼1 nm between the fatty acyl chains and the choline nitrogen, with the first water layer in the vicinity of the glycerol C3 ester linkage that has the slowest exchange rate . The hydration shells in the headgroup region can be graded by the stability of the water molecules.…”
Section: Introductionmentioning
confidence: 99%